Association of protein phosphatase PPM1G with alcohol use disorder and brain activity during behavioral control in a genome-wide methylation analysis - Ruggeri, Barbara; Banaschewski, Tobias; Flor, Herta; Rietschel, Marcella; Smolka, Michael; Spanagel, Rainer; Sommer, Wolfgang H. (The American journal of psychiatry, 2015)
Objective: The genetic component of alcohol use disorder is substantial, but monozygotic twin discordance indicates a role for nonheritable differences that could be mediated by epigenetics. Despite growing evidence associating epigenetics and psychiatric disorders, it is unclear how epigenetics, particularly DNA methylation, relate to brain function and behavior, including drinking behavior. Method: The authors carried out a genome-wide analysis of DNA methylation of 18 monozygotic twin pairs discordant for alcohol use disorder and validated differentially methylated regions. After validation, the authors characterized these differentially methylated regions using personality trait assessment and functional MRI in a sample of 499 adolescents. Results: Hypermethylation in the 3′-protein-phosphatase-1G (PPM1G) gene locus was associated with alcohol use disorder. The authors found association of PPM1G hypermethylation with early escalation of alcohol use and increased impulsiveness. They also observed association of PPM1G hypermethylation with increased blood-oxygen-level-dependent response in the right subthalamic nucleus during an impulsiveness task. Conclusions: Overall, the authors provide first evidence for an epigenetic marker associated with alcohol consumption and its underlying neurobehavioral phenotype.